A proof of principle investigation of a novel enzyme formulation on dental calculus deposition: a 4-week randomized human clinical trial - Milleman, Kimberly R.; Deener, Greg; Milleman, Jeffery L.; Mish, Barbara; Schuller, Reinhard; Mynarcik, Dennis (BMC oral health, 2024)
Background The dissolution of dental calculus, safely and at home, is among the more challenging issues facing the over-the-counter healthcare industry. Pontis Biologics, Inc. has developed novel model of calculus development and structure and has formulated a dentifrice (Tartarase™) using digestive enzymes as active ingredients that is shown to dissolve dental calculus in this Proof of Principle clinical trial. Methods This investigation was designed to evaluate the safety and efficacy of a novel enzyme formulation to remove existing calculus deposits in 4 weeks, measured using the Volpe-Manhold Index (V-MI) on lingual surfaces of 6 lower anterior teeth. The test formulation was compared to Crest Cavity Protection, as a control dentifrice. A total of 40 randomized test subjects began the study with 20 assigned to the control dentifrice and 20 assigned to the Tartarase groups (ten each, one brushing with Tartarase twice daily and one brushed with Tartarase and wore a dental tray filled with Tartarase for 30 min then brushed again with Tartarase, once daily). Results The Crest group experienced a 12% increase in calculus, in contrast to the results of both Tartarase groups that experienced a 40% reduction in calculus in 4 weeks of unsupervised at home use of the Tartarase toothpaste formulation. Conclusions This proof of principle study demonstrates that a dentifrice, formulated along the lines of the Tartarase material, is capable of combating calculus accumulation using the same oral hygiene habits that are common worldwide. Trial registration This trial was registered retrospectively at clinicaltrials.gov and has the Unique Identification Number: NCT06139835, 14/11/2023.